2005
DOI: 10.1212/01.wnl.0000163990.00057.66
|View full text |Cite
|
Sign up to set email alerts
|

Detection of common and private mutations in the COL6A1 gene of patients with Bethlem myopathy

Abstract: The clustering of the mutations in a relatively narrow area of the three collagen type VI chains in patients with Bethlem myopathy (BM) suggests that mutations in different regions could result in different phenotypes or in no phenotype at all. Moreover, the detection of mutations in only 60% of the patients suggests the existence of at least another gene associated with BM. The authors propose the direct sequencing of COL6 cDNAs as the first mutation screening analysis in BM, given the high number of exon-ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…The concept of a spectrum of collagen VI-related disorders with marked clinical and genetic heterogeneity has emerged from the recent advances on the molecular mechanism of both diseases 69 . The complex genotype/phenotype correlations that have been broadly analysed in these two conditions clearly indicate that in both collagen VI-related disorders the main pathomechanism is due to the disruption of collagen VI anchorage to the basal lamina of the muscular fibers 74,75,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] .…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of a spectrum of collagen VI-related disorders with marked clinical and genetic heterogeneity has emerged from the recent advances on the molecular mechanism of both diseases 69 . The complex genotype/phenotype correlations that have been broadly analysed in these two conditions clearly indicate that in both collagen VI-related disorders the main pathomechanism is due to the disruption of collagen VI anchorage to the basal lamina of the muscular fibers 74,75,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] .…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
“…The data from molecular analysis in Bethlem myopathy revealed that Col6A1 is the most involved gene and a splice site mutation seems to be the most common, not only in Col6A1 as also in Col6A2 and Col6A3 genes 123,124 . The α1exon 14 skipping mutation is the most commonly reported in Bethlem patients 75,121,[123][124][125] , leading to reduced amounts of collagen VI protein, some of which is structurally abnormal with an impaired ability to form microfibrils 69 .…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It is increasingly recognized that UCMD and BM are part of the same clinical spectrum, and the effect of a particular mutation on the production of collagen VI determines the severity. Interestingly, in a significant proportion of individuals affected with these myopathies, mutations in COL6A1, COL6A2, or COL6A3 cannot be found (21,22) suggesting that other molecules are involved in the pathology of these diseases.Here we report the identification and characterization of three additional collagen VI genes, COL6A4, COL6A5, and COL6A6. These genes are clustered at a single genomic locus in mammals and are located in humans on the q arm of chromo-* This work was supported in part by Deutsche Forschungsgemeinschaft SFB 492 Grant A2.…”
mentioning
confidence: 99%
“…It is increasingly recognized that UCMD and BM are part of the same clinical spectrum, and the effect of a particular mutation on the production of collagen VI determines the severity. Interestingly, in a significant proportion of individuals affected with these myopathies, mutations in COL6A1, COL6A2, or COL6A3 cannot be found (21,22) suggesting that other molecules are involved in the pathology of these diseases.…”
mentioning
confidence: 99%